Kako predstaviti Casimirjev tlak? - Likar, Andrej (Obzornik za matematiko in fiziko, 2014)
The article introduces simple derivation of Casimir pressure which could be presented in a course of basics of quantum electrodynamics. One dimensional case is introduced first which allows smooth transition to famous Casimir equation for pressure between two matal plates. We avoid calulation of energy density but start from the beginning with pressure, therefore eliminating discussion of polarization of certain standing waves. We show that regularizing function with sharp cut of high frequency region should not be used, as suggested in some textbooks.
Keywords: fizika; physics; kvantna elektrodinamika; Casimirjev tlak; Casimirjeva enačba